Nine to five : how gender, sex, and sexuality continue to define the American workplace / Joanna L. Grossman. - Grossman, Joanna L. (Cambridge University Press, 2016)
Nine to Five provides a lively and accessible introduction to the laws and policies regulating sex, sexuality, and gender identity in the American workplace. Contemporary cases and events reveal the breadth and persistence of sexism and gender stereotyping. Through a series of essays organized around sex discrimination, sexual harassment, pregnancy discrimination, and pay equity, the book highlights legal rules and doctrines that privilege men over women and masculinity over femininity. In understanding the law - what it forbids, what it allows, and to what it turns a blind eye - we see why it is far too soon to declare the triumph of working women's equality. Despite significant gains for women, gender continues to define the work experience in both predictable and surprising ways. A witty and engaging guide to the legal terrain, Nine to Five also proposes solutions to the many obstacles that remain on the path to equality.